A balancing act: An interpretive description of healthcare providers' and families' perspective on the surgical experiences of children with autism spectrum disorder. (May 2022) - Snow, Stephanie L; Smith, Isabel M; Latimer, Margot; Stirling Cameron, Emma; Fox, Jennifer; Chorney, Jill
Children with an autism spectrum disorder (autism) are vulnerable to negative experiences within the surgical setting. This qualitative study used Interpretive Description. Individual interviews were conducted with 8 parents of children with autism who had recently undergone surgery, and 15 healthcare providers (HCPs) with experience caring for children with autism. Participants were asked open-ended questions on the approaches used to support children with autism around the time of surgery and their effectiveness, how the surgical experience could be improved, and the barriers and facilitators to potential improvements. Results yielded three main themes within an overarching metaphor of a balancing act. The first theme, finding your footing through an uncertain journey, described individual factors (e.g. anticipatory anxiety) that set the foundation for surgery-related experiences. The second theme, relationships can help to keep everyone steady, highlighted how interpersonal dynamics (e.g. collaboration and empathy) influence the experience. Finally, the systems shape the experience theme captured the impact of systemic factors (e.g. the hospital environment) on the balancing act. These findings enriched our understanding of how individual, interpersonal, and systemic factors influence the surgical experiences of children with autism, families, and HCPs. Insights gained from this study can be used to inform future interventions. Lay abstract: Children with an autism spectrum disorder (autism) often have negative experiences within the surgical setting. We conducted individual interviews with 8 parents of children with autism who had recently undergone surgery, and 15 healthcare providers (HCPs) with experience caring for children with autism. We asked open-ended questions on the approaches used to support children with autism around the time of surgery, how effective they were, suggestions for improvement, and the barriers and facilitators to improvement. Three main themes emerged within an overarching metaphor of a balancing act . The first theme, finding your footing through an uncertain journey, described individual factors (e.g. anticipatory anxiety) that set the foundation for experiences. The second theme, relationships can help to keep everyone steady, highlighted how personal interactions (e.g. collaboration and empathy) influence the experience. Finally, the systems shape the experience theme captured how systemic factors (e.g. the hospital environment) affected the balancing act . These findings enriched our understanding of the surgical experiences of children with autism, families, and HCPs by demonstrating the importance of individual characteristics, relationships, and systemic factors. Future interventions should consider this complexity and intervene not just with children, but also their parents, healthcare providers, and in policy to improve experiences.